Circular Economy Biorefinery for Producing Biofertilizers, Biogas, and Bioenergy from Biomass: Conceptual Design, Process Characterization, and Thermo-Economic Assessment - Gomez Montoya, Juan Pablo; Castillo Alvarez, Yoisdel; Yepes Tumay, Hernando Alexander; Tisza Contreras, Juan Francisco; Meseth Macchiavello, Enrique (LACCEI, 2025)
To provide effective development strategies for Colombia and similar developing regions, this paper proposes the conceptual design, construction, and start-up of circular economy biorefineries using biomass (BUB) through anaerobic biodigesters. The project focuses on producing high-quality municipal biofertilizers to promote organic agriculture and generate biogas as a renewable fuel for electricity production in adapted internal combustion engines. Biogas is obtained from diverse biomass sources, mainly livestock manure and municipal organic matter (MOM), enabling a sustainable valorization of local waste streams. The implementation framework is based on a biomass circular economy (CE) model specifically designed to foster organic agricultural practices, rural reforestation initiatives, renewable fuel production, and energy self-sufficiency. This model aims to contribute to the energy transition, mitigate greenhouse gas emissions, and strengthen food sovereignty in vulnerable communities. A comprehensive thermo-economic analysis demonstrates a high rate of return on investment (ROI) and significant financial benefits by reducing dependence on carbon-intensive fuels. The results highlight the potential of this frugal innovation approach to improve local economies, create new market opportunities, and accelerate sustainable development through scalable biorefineries adapted to regional conditions.